2004
DOI: 10.1242/jeb.01281
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic power of European starlingsSturnus vulgarisduring flight in a wind tunnel, estimated from heat transfer modelling, doubly labelled water and mask respirometry

Abstract: SUMMARY It is technically demanding to measure the energetic cost of animal flight. Each of the previously available techniques has some disadvantage as well advantages. We compared measurements of the energetic cost of flight in a wind tunnel by four European starlings Sturnus vulgaris made using three independent techniques: heat transfer modelling, doubly labelled water (DLW)and mask respirometry. We based our heat transfer model on thermal images of the surface temperature of the birds and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 45 publications
3
64
0
Order By: Relevance
“…Experimental measurements of the cost of bird flight carried out in wind tunnels over many hours (Pennycuick et al, 1997;Kvist et al, 2001;Ward et al, 2004;Engel et al, 2006;SchmidtWellenburg et al, 2006;Schmidt-Wellenburg et al, 2008) also vary widely, but gravitate toward values around 9 times BMR (Videler, 2005). Migrating shorebirds have the capacity to process food and store fuel at fast rates (Kvist and Lindström, 2003) related to them usually being in a hurry and because they make such long-distance flights.…”
Section: What Do Metabolic Ceilings Represent?mentioning
confidence: 99%
“…Experimental measurements of the cost of bird flight carried out in wind tunnels over many hours (Pennycuick et al, 1997;Kvist et al, 2001;Ward et al, 2004;Engel et al, 2006;SchmidtWellenburg et al, 2006;Schmidt-Wellenburg et al, 2008) also vary widely, but gravitate toward values around 9 times BMR (Videler, 2005). Migrating shorebirds have the capacity to process food and store fuel at fast rates (Kvist and Lindström, 2003) related to them usually being in a hurry and because they make such long-distance flights.…”
Section: What Do Metabolic Ceilings Represent?mentioning
confidence: 99%
“…For many years, it appeared that the curve for P met was flat at intermediate flight speeds, which suggested that efficiency is lowest in the range of preferred flight speeds (reviewed in Ellington, 1991). Recently, efforts to measure P met using a variety of techniques including doublelabelled water, heat transfer and gas respirometry, reveal that the curve for P met is U-shaped much as that for P mus and P aero , with muscular efficiency in the range of 20% Ward et al, 2004;Engel et al, 2006;Bundle et al, 2007) (Fig.·2C). Comparison of the curves for P met and P mus in cockatiels Nymphicus hollandicus, measured in two different studies, suggests that efficiency is not constant across speeds and that V mp and V mr are both faster when measured using P met compared with P mus Bundle et al, 2007) (Fig.·2).…”
Section: Primary Flight Musclesmentioning
confidence: 99%
“…The first level is metabolic power input (P met ) to the muscles, directly of interest to a flying, foraging bird, and generally a realm of study for respiratory, thermal and chemical physiologists. P met is the rate the bird expends chemical energy to supply the flight muscles, and it may be measured using double-labeled water (Nudds and Bryant, 2000;Ward et al, 2004;Engel et al, 2006), labeled bicarbonate (Hambly et al, 2002), oxygen consumption and carbon dioxide production Ward et al, 2004;Bundle et al, 2007). P met equals the sum of mechanical power output from the muscles (P mus ) and the rate of heat loss from the muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement technique may also play a key role in defining flight power-velocity relationships. For example, Ward et al (Ward et al, 2004) assessed flight power by respirometry, doubly labeled water and heat transfer modeling in a single bird species (Sturnus vulgaris) and found a U-shaped relationship when they employed the doubly labeled water method, but a linear increase when using the other measurement techniques.…”
Section: Introductionmentioning
confidence: 99%